2017
DOI: 10.1002/jcad.12159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Attachment on Coping Efficacy, Career Decision Self‐Efficacy, and Life Satisfaction

Abstract: This study examined attachment, self‐efficacy variables, and life satisfaction of 583 undergraduate students. The type of analysis used was structural equation modeling. Findings indicated that students with greater avoidant and anxious attachment patterns reported lower levels of career decision self‐efficacy and coping efficacy, which then had a positive relationship with life satisfaction. Implications for theory, research, and practice were provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
(110 reference statements)
1
16
0
Order By: Relevance
“…According to previous research on the social cognitive career theory, CDSE plays a key role in career planning and development (Chui et al, 2020;Gushue and Whitson 2006;Lent et al 2001Lent et al , 2003Lent et al , 2005. In both Western and Eastern cultures, CDSE is also strongly influenced by parenting styles (Ginevra et al, 2015;Guan et al, 2016;Kiadarbandsari et al, 2016;Liu et al, 2015;Lustig et al, 2017;Roman et al, 2015;Wright et al, 2017). Fouad et al (2010, in Sovet andMetz 2014) affirmed the family affects an individual's career-related decisions, through the provision of information and emotional and financial support.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research on the social cognitive career theory, CDSE plays a key role in career planning and development (Chui et al, 2020;Gushue and Whitson 2006;Lent et al 2001Lent et al , 2003Lent et al , 2005. In both Western and Eastern cultures, CDSE is also strongly influenced by parenting styles (Ginevra et al, 2015;Guan et al, 2016;Kiadarbandsari et al, 2016;Liu et al, 2015;Lustig et al, 2017;Roman et al, 2015;Wright et al, 2017). Fouad et al (2010, in Sovet andMetz 2014) affirmed the family affects an individual's career-related decisions, through the provision of information and emotional and financial support.…”
Section: Introductionmentioning
confidence: 99%
“…Gnilka, Ashby, and Noble (2013) indicated that attachment anxiety and attachment avoidance were both negatively correlated with life satisfaction [46]. Another study found that both anxious and avoidant attachment had small negative direct effects on life satisfaction [47].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, domain satisfaction is an important pathway for enhancing life satisfaction, and several studies with culturally diverse college students have found a positive relation between academic satisfaction and life satisfaction (Lent et al, 2011; Lent et al, 2017; Lent, Taveira, & Lobo, 2012; Lent et al, 2014; Lent, Taveira, Sheu, & Singley, 2009; Ojeda, Flores, & Navarro, 2011). Recent research with college students outside of the engineering domain has identified career support (Jiang et al, 2017) as a predictor of life satisfaction and coping efficacy (Wright, Firsick, Kacmarski, & Jenkins-Guarnieri, 2017) as a mediating variable in the relationship between attachment and life satisfaction. We explore whether the findings of these recent studies (Jiang et al, 2017; Wright et al, 2017) extend to the engineering domain.…”
Section: Life Satisfactionmentioning
confidence: 99%
“…Recent research with college students outside of the engineering domain has identified career support (Jiang et al, 2017) as a predictor of life satisfaction and coping efficacy (Wright, Firsick, Kacmarski, & Jenkins-Guarnieri, 2017) as a mediating variable in the relationship between attachment and life satisfaction. We explore whether the findings of these recent studies (Jiang et al, 2017; Wright et al, 2017) extend to the engineering domain.…”
Section: Life Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation